ANALYSIS OF SUPPLY CHAIN MANAGEMENT ACTIVITIES (CASE STUDY ON ZASKIA FURNITURE BUSINESS IN PALU CITY) - Pramudya, Ady; Zainudin, F; Syamsuddin; Hadi, S (Magister Manajemen of Universitas Islam Nahdlatul Ulama Jepara, 2024)
This research aims to identify and analyze the supply chain flow at Zaskia Furniture located on Jl. R.E Martadinata, Layana Indah Village, North Palu District, Palu City. The paradigm employed in this research is the constructivism paradigm, utilizing a qualitative descriptive approach. The study involved a total of 9 informants, and data collection was carried out by directly conducting interviews with them in the field. The data analysis method utilized in this research is the NVivo 12 Plus software. The results of this study indicate that the supply chain at Zaskia Furniture is interconnected with the upstream, internal, and downstream supply chain pathways. The upstream supply chain is associated with the procurement of raw materials originating from Tibo Village, West Coast. The types of wood used include bayur, cempaka, and inje. The internal supply chain is related to the production process, revealing that the production stage at Zaskia Furniture is executed by 4 employees responsible for various production processes. The downstream supply chain is associated with distributing the final products to consumers, accomplished through two channels: direct distribution to end consumers and indirect distribution through retailers. The supply chain management at Zaskia Furniture is functioning well, but it is not yet optimal, indicating the need for some evaluations.